2019
DOI: 10.1681/asn.2018111166
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Albuminuria But Not GFR are Associated with Early Changes in Kidney Structure in Type 2 Diabetes

Abstract: BackgroundIn type 1 diabetes, changes in the GFR and urine albumin-to-creatinine ratio (ACR) are related to changes in kidney structure that reflect disease progression. However, such changes have not been studied in type 2 diabetes.MethodsParticipants were American Indians with type 2 diabetes enrolled in a clinical trial of losartan versus placebo. We followed a subset who underwent kidney biopsy at the end of the 6-year trial, with annual measurements of GFR (by urinary clearance of iothalamate) and ACR. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 43 publications
2
43
0
Order By: Relevance
“…A follow-up study with repeated kidney biopsies in Japanese type 2 diabetic patients with and without microalbuminuria reported a correlation between mesangial matrix deposition and GFR loss, while there was no correlation with albuminuria [28]. A similar study performed in Pima Indians with, on average, normoalbuminuria and elevated GFR, showed no correlation between glomerular lesions and very modest GFR decline, while there was a correlation with albumin-to-creatinine ratio [29]. However, in a Pima Indian cohort with type 2 diabetes with higher baseline levels of albuminuria, 46% of whom developed renal function loss ≥ 40%, classical DN glomerulopathy lesions, especially mesangial expansion, were strongly predictive of this progression [30].…”
Section: Type 2 Diabetesmentioning
confidence: 95%
See 1 more Smart Citation
“…A follow-up study with repeated kidney biopsies in Japanese type 2 diabetic patients with and without microalbuminuria reported a correlation between mesangial matrix deposition and GFR loss, while there was no correlation with albuminuria [28]. A similar study performed in Pima Indians with, on average, normoalbuminuria and elevated GFR, showed no correlation between glomerular lesions and very modest GFR decline, while there was a correlation with albumin-to-creatinine ratio [29]. However, in a Pima Indian cohort with type 2 diabetes with higher baseline levels of albuminuria, 46% of whom developed renal function loss ≥ 40%, classical DN glomerulopathy lesions, especially mesangial expansion, were strongly predictive of this progression [30].…”
Section: Type 2 Diabetesmentioning
confidence: 95%
“…Overall, these data suggest that in type 2 diabetic patients podocyte loss and changes in podocyte structure occur from the early stages of diabetic nephropathy and might help to understand the nature of albuminuria, especially in those without the classic diabetic glomerular lesions. However, more recent studies in Pima Indian research kidney biopsy subjects with type 2 diabetes found no predictive value of podocyte numerical density on early changes in albumin excretion or measured GFR nor was podocyte number per glomerulus predictive of 40% or more GFR loss [29,30]. Clearly, more work is needed on this important cell in DN.…”
Section: Type 2 Diabetesmentioning
confidence: 98%
“…Albuminuria is the common clinically manifestation of DN that usually develops before the glomerular filtration rate (GFR) impaired and increases the risk of decline of GFR (Molitch et al, 2010), the prevention of albuminuria is therefore a recommendatory therapy in patients with DN (Looker et al, 2019). Podocyte play a key role in the pathogenesis of DN (Denhez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The morphological changes in the structure of the kidney are observed early on, before DKD is clinically characterized, indicating that renal biopsies would be highly beneficial in diagnosing DKD [ 40 ]. The structural changes in the kidney are associated with the clinical progression of the disease in both T1D and T2D [ 41 , 42 ], and interestingly, in people with T2D, the changes in albuminuria, but not in GFR, were found to associate with the early structural changes in the kidney [ 42 ].…”
Section: Diabetic Kidney Diseasementioning
confidence: 99%